2016
DOI: 10.2118/184386-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Paraffin Deposition Under Two-Phase Gas/Oil Slug Flow in Horizontal Pipes

Abstract: Summary Paraffin or wax deposition under two-phase gas/oil slug flow in horizontal pipes is studied experimentally. The experiments are conducted by use of a 2.067-in., large-scale multiphase flow loop under an operating pressure of 350 psig. Testing fluids are Garden Banks condensate and natural gas. Two-phase-flow hydrodynamics and single-phase paraffin-deposition experiments are conducted and used as base cases for a comprehensive data analysis. Deposition experiments are conducted with param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…They showed that the turbulent flow wax deposit surface is visually smooth away from the inlet but there was a no-deposition zone and a patchwork zone near the test section inlet. Furthermore, Rittirong et al , recently confirmed that the single-phase turbulent and two-phase gas-oil slug flow had the visually smooth deposit surface for the region away from the test section inlet. In this case, they used a much longer test section and Garden Banks condensate (same fluid as in this study), instead of South Pelto crude oil …”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…They showed that the turbulent flow wax deposit surface is visually smooth away from the inlet but there was a no-deposition zone and a patchwork zone near the test section inlet. Furthermore, Rittirong et al , recently confirmed that the single-phase turbulent and two-phase gas-oil slug flow had the visually smooth deposit surface for the region away from the test section inlet. In this case, they used a much longer test section and Garden Banks condensate (same fluid as in this study), instead of South Pelto crude oil …”
Section: Introductionmentioning
confidence: 90%
“…The condensate density at ∼12 psig (discharge pressure) was measured continuously, using a Coriolis flow meter (Micro Motion F100S), and was found to be ∼835 ± 1.5 kg/m 3 at 77 ± 0.2 °F. The WAT and n-C30+ fraction of oil (oil wax content, the wax fraction that participates in the wax deposition process for the set point used in this study) are 96 °F and 0.4% (w/w), respectively (complete composition data are given in Appendix A). The condensate viscosity was determined based on the pressure drop method and found to be consistent with the data reported in the works of Mirazizi and Rittirong, within the uncertainty of the measurement.…”
Section: Experimental Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate prediction of the wax deposition process in a crude oil pipeline can help for timely planning of the pigging operation or hot oil circulation process to minimize production loss and ultimately economic losses. The predictions of the amount of wax deposition in the pipelines from available models 14 − 18 do not match with the field observations. Sometimes, even these predictions fail to match the data generated in the laboratory using flow loops, as shown in Table 1 .…”
Section: Introductionmentioning
confidence: 84%
“…However, crude oil is a multicomponent system, and a specie diffusion coefficient based on different n -alkanes and their amount should be utilized for better prediction purposes. Thus, there is a need to investigate and understand the wax deposition process in crude oil pipelines (experimental flow loops and field pipelines) along with the verification of available predictive models 14 − 18 for field pipelines. 5 A simple predictive tool, along with upscaling parameters, is required for accurate prediction of the wax deposition process in a crude oil pipeline.…”
Section: Introductionmentioning
confidence: 99%